Local Wisdom-Based School Literacy Movement and Elementary Students' Critical Reading Skills - Lailiya, Nirmala Rahmatul; Sukartiningsih, Wahyu; Hendratno, Hendratno (Papanda Publisher, 2025)
This study analyzes the effectiveness of integrating local wisdom